Engineering Characteristics of Fully Weathered Soft Rock Filling and Settlement Analysis of High Fill Embankment - GUO Zhiyu; ZHANG Rong; ZHENG Bowen; NAN Kai; LI Sha (Renmin Zhujiang)
To study the engineering characteristics of fully weathered soft rock filling,we carried out indoor bearing ratio tests and compression tests on the fully weathered soft rock with compaction degrees of 96%,94% and 93% respectively.On this basis,we conducted a numerical simulation on the high fill embankment as its special filled section.The results show that the expansion rate of the fully weathered soft rock is1.29%~1.87%,indicating that it does not belong to expansive soil.The CBR value also tends to increase when the compaction degree gets higher.Its value meets the specification requirements,making it able to be used as embankment filling.The compression modulus is enhanced with the increase in compaction degree,and the wetting deformation rates corresponding to different compaction degrees are2.03%,3.24% and3.86%,respectively,which are not high generally.The settlement trend of high fill embankment made of soft rock is increasing first and then decreasing with the increase in depth and peaks at1/3 of the embankment height.As the compaction degree of the high fill embankment is elevated,the settlement is reduced gradually,but the difference is not big.With the increase in stone content,the settlement first decreases and then increases and is minimized when the stone content is 55%.Therefore,it is not economical to reduce embankment settlement by increasing compaction degree during soft rock filling,while enhancing the stone content to about 55% is a good choice instead.